2022
DOI: 10.1177/0271678x221098503
|View full text |Cite
|
Sign up to set email alerts
|

Early disturbance of dynamic synchronization and neurovascular coupling in cognitively normal Parkinson’s disease

Abstract: Pathological process in Parkinson’s disease (PD) is accompanied with functional and metabolic alterations. The time-varying properties of functional coherence and their coupling to regional perfusion are still rarely elucidated. To investigate early disruption of dynamic regional homogeneity (dReho) and neurovascular coupling in cognitively normal PD patients, dynamic neuronal synchronization and regional perfusion were measured using dReho and cerebral blood flow (CBF), respectively. Neurovascular coupling wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…It requires collaboration among many components in the brain, including neurons, glial cells, smooth muscle cells, and endothelial cells. Any impairment in these components can lead to an abnormal NVC, affecting homeostasis (Guo et al., 2019; Li et al., 2021; Shang et al., 2022; Zhu et al., 2022). Generally, NVC in a healthy brain actively regulates the blood supply according to the local neuronal activity intensity, maintaining a relatively stable microenvironment for neurons.…”
Section: Discussionmentioning
confidence: 99%
“…It requires collaboration among many components in the brain, including neurons, glial cells, smooth muscle cells, and endothelial cells. Any impairment in these components can lead to an abnormal NVC, affecting homeostasis (Guo et al., 2019; Li et al., 2021; Shang et al., 2022; Zhu et al., 2022). Generally, NVC in a healthy brain actively regulates the blood supply according to the local neuronal activity intensity, maintaining a relatively stable microenvironment for neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed abnormal temporal property of local neural activity in the visual, sensorimotor, and cognitive systems in PD, which was consistent with the previous studies. For example, the previous fMRI studies that calculated the variability of brain signal across time found abnormal variance in visual [47][48][49] , sensorimotor 47,50 , and frontal 51,52 regions in PD. Some studies also found that the symptom severity of PD significantly correlated with such abnormal variability in the visual and sensorimotor regions.…”
Section: Discussionmentioning
confidence: 99%
“…ReHo primarily measures the temporal synchrony of regional neural activity between spatially adjacent regions ( 22 ), and dReHo reflects the change in similarity between the time series of a specific voxel and its nearest neighbors ( 42 , 43 ). Patients with TA had increased dReHo values in the Left superior temporal gyrus, middle frontal gyrus, precentral gyrus, precuneus, angular gyrus, right superior frontal gyrus, middle temporal gyrus, postcentral gyrus, middle frontal gyrus.…”
Section: Discussionmentioning
confidence: 99%